Guidelines for conducting split-mouth clinical studies in restorative dentistry - Zanatta, Rayssa Ferreira; Silva, Tania Mara da; Esper, Maria Angela Lacerda Rangel; Bresciani, Eduardo; Caneppele, Taciana Marco Ferraz; Gonçalves, Sergio Eduardo de Paiva (Brazilian Dental Science, 2017)
The split-mouth design used in some clinical trials make a randomization scheme on site level where two treatments are randomly assigned to sites of one of the two halves of the mouth. The aim of this review was to summarize guidelines for conducting split-mouth clinical studies in Restorative Dentistry. This is a review performed through scientific articles published between 2004 and 2014 indexed in MEDLINE, PubMed and Scielo databases. The study evaluated USPHS and FDI criteria. The current review showed the main characteristics used in split-mouth studies presented the Restorative Dentistry literature, as ethical aspects, sample calculation, methods of selection and evaluation patients, in order to provide a guideline for clinical conduction. It showed a standard of methodologies to enable comparison among studies. Keywords: Clinical studies, split-mouth design, dentistry.